Green manure associated with rock-phosphate on maize crop - de Araújo, Adelson Paulo; de Almeida, Dejair Lopes (Pesquisa Agropecuaria Brasileira, 1993)
The experiment was carried out on a Red-Yellow Podzolic distrophic soil (Typic Haplustult), with the objective of evaluating the effect of green manure with jackbean (Canavalia ensiformis (L.) DC.), associated with patos-de-minas rock-phosphate and superphosphate (at a level of 200 kg of total P2O5/ha), on maize crop. The phosphate fertilization did not affect the nodulation and the contents of N and K incorporated by jackbean, but increased the shoot dry matter, the contents of P, Ca, and Mg incorporated, and the mycorrhizal colonization. The green manure increased maize yield as much as the fertilization with 80 kg N/ha on urea form, when compared to the controls. The green manure increased the mycorrhizal colonization on corn, and the available K on superficial soil. The superphosphate and rock-phosphate had the same effect on improving the yield and the foliar P concentration on corn, probably due to the water deficit registered on the tillage. No significant interactive effect between green manure and phosphate fertilization was shown.